Linguistic Politeness in Digital Academic Communication: Lecturer-Student Whatsapp Interaction at Universitas Terbuka - Hilma Erfiani Baroroh; Ifan Iskandar; Miftahulkhairah Anwar (UIN Raden Mas Said Surakarta, Indonesia, 2026)
The digital transformation of higher education has fundamentally reshaped academic communication, particularly in Distance Higher Education (DHE) institutions. This study investigates linguistic politeness in lecturer–student WhatsApp interactions at Universitas Terbuka, Indonesia. Using a qualitative instrumental case study approach, 851 WhatsApp messages representing seven communicative genres were analyzed. The study contributes by proposing the Indonesian Academic Digital Politeness Model (IADPM), an integrative framework that explains how linguistic politeness is shaped by communicative genre, sociocultural norms, digital affordances, and institutional power within Indonesian digital academic communication. The findings show that students predominantly employ Extreme Negative Politeness through apologies and honorific expressions, whereas lecturers rely on Bald On-Record strategies legitimized by institutional authority. The folded hands emoji functions as a digital marker of respect, while platform features such as blue ticks reinforce institutional accountability and hierarchical relationships. These findings demonstrate that asynchronous digital communication does not diminish academic hierarchy but instead reconfigures its expression through culturally embedded digital practices. The study recommends the development of institutional guidelines for digital academic communication to promote more effective and culturally appropriate interactions in online higher education. Transformasi digital dalam pendidikan tinggi telah secara fundamental mengubah komunikasi akademik, khususnya di institusi Pendidikan Tinggi Jarak Jauh (Distance Higher Education/DHE). Studi ini mengkaji kesantunan berbahasa dalam interaksi WhatsApp antara dosen dan mahasiswa di Universitas Terbuka, Indonesia. Dengan menggunakan pendekatan studi kasus instrumental kualitatif, sebanyak 851 pesan WhatsApp yang merepresentasikan tujuh genre komunikatif dianalisis.Penelitian ini memberikan kontribusi dengan mengusulkan Indonesian Academic Digital Politeness Model (IADPM), sebuah kerangka integratif yang menjelaskan bagaimana kesantunan berbahasa dibentuk oleh genre komunikasi, norma sosiokultural, afordansi digital, dan relasi kuasa institusional dalam komunikasi akademik digital di Indonesia. Hasil penelitian menunjukkan bahwa mahasiswa didominasi oleh strategi Extreme Negative Politeness melalui penggunaan ungkapan permohonan maaf dan ekspresi honorifik, sedangkan dosen lebih banyak menggunakan strategi Bald On-Record yang dilegitimasi oleh otoritas institusional. Emoji tangan berdoa berfungsi sebagai penanda digital penghormatan, sementara fitur platform seperti blue ticks memperkuat akuntabilitas institusional dan relasi hierarkis. Temuan ini menunjukkan bahwa komunikasi digital asinkron tidak mengurangi hierarki akademik, melainkan merekonfigurasi ekspresinya melalui praktik digital yang berakar pada budaya. Studi ini merekomendasikan pengembangan pedoman institusional untuk komunikasi akademik digital guna mendorong interaksi yang lebih efektif dan sesuai budaya dalam pendidikan tinggi daring.